2018
DOI: 10.1007/s11596-018-1979-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Predictive Model Related to Pathogen Invasion for Infectious Diseases and Its Diagnostic Value in Fever of Unknown Origin

Abstract: The present study aimed to establish a list of parameters indicative of pathogen invasion and develop a predictive model to distinguish the etiologies of fever of unknown origin (FUO) into infectious and non-infectious causes. From January 2014 to September 2017, 431 patients with FUO were prospectively enrolled in the study population. This study established a list of 26 variables from the following 4 aspects: host factors, epidemiological factors, behavioral factors, and iatrogenic factors. Predefined predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 27 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…Seven studies utilized a structured diagnostic protocol [ 7–9 , 17 , 19 , 23 , 24 , 31 ]. Nine studies [ 7–9 , 17–21 , 30 , 31 ] (47.4%, total n = 1268) used Peterdorf’s criteria [ 5 , 11 ] for FUO, 7 studies [ 2 , 23 , 24 , 26 , 28 , 29 , 32 ] (36.8%, total n = 1135) used Durack’s criteria [ 6 , 11 ], and 3 studies [ 22 , 25 , 27 ] (15.8%, total n = 264) used either criterion. There were 1049 (39.3%) infections, 568 (21.3%) NIIDs, and 404 (15.1%) cancers with 1236 (46.3%) total female participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies utilized a structured diagnostic protocol [ 7–9 , 17 , 19 , 23 , 24 , 31 ]. Nine studies [ 7–9 , 17–21 , 30 , 31 ] (47.4%, total n = 1268) used Peterdorf’s criteria [ 5 , 11 ] for FUO, 7 studies [ 2 , 23 , 24 , 26 , 28 , 29 , 32 ] (36.8%, total n = 1135) used Durack’s criteria [ 6 , 11 ], and 3 studies [ 22 , 25 , 27 ] (15.8%, total n = 264) used either criterion. There were 1049 (39.3%) infections, 568 (21.3%) NIIDs, and 404 (15.1%) cancers with 1236 (46.3%) total female participants.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the ages of participants ranged from 10 to 94 years. Undiagnosed cases were reported in all but 2 studies [ 29 , 30 ] (n = 616) and occurred in 449 of 2051 (21.9%) cases. The contribution of PDCs, biochemical and immunological serology, and microbiology cultures, as well as histological and imaging studies, was insufficiently reported in several studies for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sample consisted of 2627 participants, of whom 11.7% to 58.6% had an infectious diseases etiology, 6.0% to 34.0% had a noninfectious inflammatory disorder, and 2.9% to 30.1% had an underlying oncologic condition. Undiagnosed cases were reported in all but 2 studies 27 , 29 and ranged from 6.9% to 50.7%. Nine studies 1 , 2 , 6 , 15 , 16 , 17 , 18 , 19 , 29 , 30 with 1228 of the 2627 total participants (46.7%) used the criteria of Peterdorf and Beeson 4 to classify FUO, and 7 studies 21 , 22 , 24 , 26 , 27 , 28 , 31 combining 1135 participants (43.2%) were classified by the criteria of Durack and Street.…”
Section: Resultsmentioning
confidence: 99%